POLITIK HUKUM PEMBERIAN HAK GUNA USAHA SETELAH BERLAKUNYA UNDANG-UNDANG PENANAMAN MODAL NOMOR 25 TAHUN 2007 DAN IMPLIKASINYA TERHADAP NASIB PETANI - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2009)
Application policy of Investment Act (Undang-Undang Penanaman Modal/UUPM) Number 25 of 2007 about Capital investment can bring negative implication to fate of farmer. UUPM hardly clearly gives amenity to investor to obtain farm and tends to give the big trust to investor to build the economic of Indonesia. The amenitys that is given to investor can be misused if there is not followed by readiness of the law structure with having enough ability to implement the substance of UUPM causing can give the negative implication to fate of farmer. Until now, the implementation of vesting policy of HGU still has many harvesting problem between entrepreneurs with public that occupying on the area around of HGU. The application of policy that applying of vesting of HGU after implementing of UUPM has give ever greater gain to entrepreneur because the duration of domination of extendable HGU at the first time. The Government needs to take the normatif of rule that remain to the farmer to gets justice and prosperity while investor still can inculcate the legal capital and has the business in Indonesia. In this case, the law structure prepared to beginning of UUPM must really brood in order not to invite abuse to vesting of HGU to investor. This thing is enabled by HGU that can be transferred or transferred to other party according to PP Nomor 40 Tahun 1996, while UUPM only arrange the duration of vesting of HGU. Visible capital investment act as indication that there is no motivation for economics independence of public, the policy takers doesnt believe the Indonesian farmer can build plantation, agriculture and fishery or even is improved to become company. This act exactly trusts in investor that is most accurate cluster in giving the huge of land, whereas Indonesian farmer becomes cheap labour only. This is the main characteristic of colonial agrarian law that reanimated on behalf of INVESTMENT. Our farmer is not really poor